How does it end? Endpoints of boundaries lead to completion in macro-events. - Candan Şimşek, Ayşe; Aydın, Tolgahan; Huff, Markus (Memory & Cognition, 2025)
While watching someone kicking a ball, missing moments of ball contact can be incorrectly identified as seen if the event is continued in a causal manner (i.e., the ball flying off). Does event completion also occur for events of a larger scale such as having breakfast (macro-event), which consists of multiple sub-steps like toasting bread (micro-event)? We conducted two experiments to measure event completion in macro-events presenting portions of multiple micro-events. In Experiment 1, video summaries were formed with or without event boundary information where a macro-end was either present or absent. Macro-end signified an overarching goal achievement that signaled the completion of previous tasks (such as leaving the kitchen with a full breakfast plate). More completion occurred for summaries with event boundary information and macro-ends. In Experiment 2, we tested two alternative hypotheses to explore the underlying process by showing the beginnings or ends of a micro-event. While the predictive processing hypothesis suggests that event completion is based more on predicting the future states of the event based on beginning information, the backward inferences hypothesis suggests that event completion relies more on deductions formed after the fact based on event endings. Results of Experiment 2 suggest that the ends of event boundaries lead to more event completion, possibly due to their role in forming causal connectivity. These results help to further understand event completion on a macro level.